2000
DOI: 10.1128/mcb.20.1.187-195.2000
|View full text |Cite
|
Sign up to set email alerts
|

The Orphan Nuclear Receptor SHP Inhibits Hepatocyte Nuclear Factor 4 and Retinoid X Receptor Transactivation: Two Mechanisms for Repression

Abstract: The orphan nuclear hormone receptor SHP interacts with a number of other nuclear hormone receptors and inhibits their transcriptional activity. Several mechanisms have been suggested to account for this inhibition. Here we show that SHP inhibits transactivation by the orphan receptor hepatocyte nuclear factor 4 (HNF-4) and the retinoid X receptor (RXR) by at least two mechanisms. SHP interacts with the same HNF-4 surface recognized by transcriptional coactivators and competes with them for binding in vivo. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

19
203
2
10

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 297 publications
(234 citation statements)
references
References 55 publications
19
203
2
10
Order By: Relevance
“…The primary basis for this effect is the induction of SHP by FXR in the presence of elevated bile acid levels, inhibiting transactivation by the nuclear receptors liver receptor homolog-1 (LRH-1) and possibly hepatocyte nuclear factor 4 alpha (HNF4␣) and repressing expression of Cyp7A1, the rate-limiting enzyme of bile acid biosynthesis, as well as a number of other bile acid biosynthetic enzymes. 7,8,[23][24][25] This function of SHP has been strongly supported by results with Shp Ϫ/Ϫ mice, which reveal defective repression in response to synthetic FXR agonists 10,11 or very short term dietary bile acid treatment. 26 However, such studies have also demonstrated the importance of SHP-independent pathways that can efficiently repress Cyp7A1 and other negative targets in response to longer term treatments with dietary bile acids.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The primary basis for this effect is the induction of SHP by FXR in the presence of elevated bile acid levels, inhibiting transactivation by the nuclear receptors liver receptor homolog-1 (LRH-1) and possibly hepatocyte nuclear factor 4 alpha (HNF4␣) and repressing expression of Cyp7A1, the rate-limiting enzyme of bile acid biosynthesis, as well as a number of other bile acid biosynthetic enzymes. 7,8,[23][24][25] This function of SHP has been strongly supported by results with Shp Ϫ/Ϫ mice, which reveal defective repression in response to synthetic FXR agonists 10,11 or very short term dietary bile acid treatment. 26 However, such studies have also demonstrated the importance of SHP-independent pathways that can efficiently repress Cyp7A1 and other negative targets in response to longer term treatments with dietary bile acids.…”
Section: Discussionmentioning
confidence: 55%
“…20 It is a transcriptional repressor and exerts its regulatory functions through protein-protein interactions with other nuclear hormone receptors and possibly other transcription factors, which can inhibit or even reverse their transactivation. [20][21][22][23][24][25] Regulation of bile acid metabolism is the most prominent of a number of physiological roles proposed for SHP. The primary basis for this effect is the induction of SHP by FXR in the presence of elevated bile acid levels, inhibiting transactivation by the nuclear receptors liver receptor homolog-1 (LRH-1) and possibly hepatocyte nuclear factor 4 alpha (HNF4␣) and repressing expression of Cyp7A1, the rate-limiting enzyme of bile acid biosynthesis, as well as a number of other bile acid biosynthetic enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we did not observe changes of HNF4␣ mRNA in SHP Ϫ/Ϫ and OB/SHP Ϫ/Ϫ livers as compared with their littermates, although SHP was reported to be a negative regulator for HNF4␣. 37 These observations suggest that HNF4␣ is unlikely the intermediate factor by which SHP regulates MTP transcription. We found that the orphan receptor LRH-1 can also bind to the MTP promoter and increase MTP expression in hepatocytes, and that this transactivation is repressed by SHP.…”
Section: Discussionmentioning
confidence: 80%
“…SHP activation by FXR ligands in hepatocytes leads to the repression of cholesterol 7␣-hydroxylase expression, the rate-limiting enzyme in the neutral pathway that leads to bile acid production from cholesterol (33). SHP is also a known target for other nuclear receptors, including the estrogen receptors and PPAR␥ (65,66), and is essential in the regulation of the expression/activity of hepatocyte NF4 and retinoid X receptor (66). A body of evidence suggest that SHP represents an important mediator of FXR activity and acts as a corepressor of FXR target genes in different physiological contexts (33,36,46,47).…”
Section: Discussionmentioning
confidence: 99%